Doing things together: adolescent health and family rituals. Issue 2 (1st February 2002) - Compañ, E; Moreno, J; Ruiz, M T; Pascual, E
Abstract : Study objectives: (1) To describe the union and life cycle of family rituals, such as specific habits of sharing daily meals, special events or other family activities, and (2) to analyse the relation between the practice of family rituals and the use by adolescents of mental health related ambulatory care services. Design: A cross sectional study. Setting: A public mental health care outpatient clinic, secondary educational centres and Alicante University (School of Social Workers and Nursing School) in Spain. Participants: A total of 282 living at home youngsters were included in the study. The case group, n=82, was sequential and consecutively drawn from the first consultation in a public mental health outpatient clinic attending a downtown area of Alicante. The comparison group (n=213) was made up of a conglomerate from various educational centres in the same metropolitan area. Main results: There was a significant difference (p=0.027) between the frequencies with which parents ate together with their offspring in the two study groups. The families of the adolescents comparison group significantly (p=0.00007) shared more family celebrations than the case group—also, the extended family was included more frequently. Moreover, differences between both groups were found in other activities and situations—adolescents in the case group reported carrying out less family activities than the adolescents in the comparison group (p=0.00001). The lower level of satisfaction in the adolescent's perception of family function led to a higher probability of presenting mental health complaints (p=0.00001). Conclusions: The youngsters with mental health complaints ate less frequently with both parents than the youngsters in the comparison group. They also shared less activities and practised less family rituals—union and life cycle—than the families of the youngsters in the comparison group, and showed a lower level of satisfaction in perceived family function.